Case Report: Diagnostic Value of Metagenomics Next Generation Sequencing in Intracranial Infection Caused by Mucor - Liu, YuChen; Zhang, Jun; Han, Bing; Du, LiJuan; Shi, ZhaoYang; Wang, ChunCheng; Xu, Min; Luo, YongGang (Frontiers in Medicine, 2021)
mNGS, as a novel culture-independent approach, demonstrated the capability of rapid, sensitive, and accurate pathogen identification. At present, there have been many case reports about the use of mNGS to assist in the diagnosis of bacterial, fungal, viral and parasitic infections and to guide clinicians to determine appropriate treatment. However, the clinical understanding of this technique is not comprehensive, and the experience of using it is relatively limited. We reported a 53-year-old man who was admitted to hospital with a high fever and headache. His inflammatory biomarkers were markedly elevated. Based on the clinical presentation, He was initially diagnosed as having an intracranial infection of unknown etiology and received empirical antibiotics and systemic supportive treatment. But these did not relieve his symptoms. Both the blood and CSF specimens were examined using traditional culture, serological testing, and mNGS. Traditional culture and serological testing produced negative results, while the mNGS revealed the presence of a potential pathogen, mucormycosis, in the CSF specimen. Then targeted antibiotic treatment was selected quickly and his temperature gradually returned to normal. Thus, we report the case in which mNGS was an auxiliary method to diagnose mucormycosis，and discuss this case in combination with relevant literature, in order to improve the clinical cognition of this technology.